Analysis of the territorial efficiency of European Funds as an instrument to reduce labor gender differences - Miguel Blanco; Lydia Bares; Oksana Hrynevych; Marcos Ferasso (Economies, 2021)
Gender equality has been one of the goals of the European Union since 1957. Article 157 of the Treaty on the Functioning of the European Union authorizes the European Parliament and the Council to adopt all those measures that guarantee the application of the principle of equality opportunities and equal treatment for men and women in employment and occupation matters. The main goal of this article was to determine whether the use of European Funds by Eurozone countries has made it possible to reduce labor differences in gender matters. To this end, the efficiency levels of the Funds are analyzed in two different periods, 2007 to 2013 and 2014 to 2020. Data Envelopment Analysis (DEA), a methodology frequently used by researchers in efficiency analyses, was applied. Among the main conclusions obtained are that the efficiency levels from the period 2014 to 2020 have been higher than that obtained in the previous period, but there are significant and persistent differences over time in the levels of gender efficiency between the different countries of the Eurozone.
Keywords: C61; J08; R58; D24; F55; 330; Data Envelopment Analysis (DEA); employment; gender